Pengaruh Motivasi, Kreativitas dan Mata Kuliah Startup Terhadap Minat Mahasiswa Membangun Startup (Studi Pada Mahasiswa Prodi Manajemen Angkatan 2018 Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Tri Dewi Nur Hidayah; Jeni Susyanti; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted to determine the effect of motivation, creativity and startup courses on students' interest in building startups partially. This research is a type of explanatory research that explains the causal relationship between the independent variable and the dependent variable through a hypothesis. The population used in this study were active students of the 2018 class of management study program, FEB, Islamic University of Malang, amounting to 518 students. In this study using a sample of 84 respondents, the sampling technique used in this study was a purposive sampling technique. This study uses quantitative methods, data acquisition using primary data with data collection using a questionnaire method through distributing questionnaires with a Likert scale as a measuring tool for respondents' answers. The data analysis method used is multiple linear regression analysis. The results of this study indicate that motivation has a positive and significant effect on student interest in building startups, creativity has a positive and significant effect on student interest in building startups and startup courses have a positive and significant effect on student interest in building startups in management study program students batch 2018 Faculty of Economics and Business Islamic University of Malang. Keyword: Motivation, Creativity, Startup Courses On Student And Interest In Building Startups